Profile of incidental exposures to e-cigarette liquids in Europe, 2018–2019. (June 2021) - Vardavas, Constantine I; Girvalaki, Charis; Odani, Satomi; Nikitara, Katerina; de Vries, Irma; van Riel, Antoinette; van Sommeren-de Potter, Iris; Grass, Johanna Nordmark; Grassi, Maria Caterina; Deim, Szilvia; Balázs, Andrea; Fosztó, Szabolcs; et al.
Background: Following the implementation of the European Union Tobacco Product Directive (EU TPD) regulations on e-cigarette products in 2016, we assessed the current profile of e-cigarette liquid exposure incidents and their associated health outcomes. Methods: De-identified data were received from poison centers in eight EU Member States (Sweden, the Netherlands, Italy, Hungary Austria, Finland, Spain and Croatia) reporting on e-cigarette liquid exposure incidents between August 2018 to December 2019. Descriptive analysis was conducted to present incident characteristics and health outcomes. Chi-square tests and multivariable logistic regression analysis were used to test associations. Results: Of the 223 e-liquid exposure incidents recorded by poison centers in multiple EU MS, 64.7% of the cases were unintentional exposures, ranging from 48.4% among adults aged ≥19 years to 100.0% among children aged 0–5 years (p < 0.05). The most frequent route of exposure was ingestion (73.5%) while55.2% experienced any clinical symptoms, including nausea (16.6%), vomiting (11.1%), and dizziness (9.0%). 57.8% of the cases were treated at the residence or on-site. Conclusion: Further monitoring is warranted, using uniform reporting requirements, to ensure the continued compliance to the EU TPD and assess its long-term impact on related incident characteristics.